New species and records of Sericini of India (Coleoptera: Scarabaeidae: Melolonthinae) III - Bhunia, Debika; Gupta, Devanshu; Chandra, Kailash; Ahrens, Dirk (Zootaxa, 2022)
Here we describe two new species from India: Neoserica panchmariensis Bhunia, Gupta, Chandra & Ahrens, new species and N. debasriae Bhunia, Gupta, Chandra & Ahrens, new species. Moreover, Maladera pseudohongkongica Ahrens & Fabrizi, 2016 is recorded from Jharkhand state of India for the first time. Species morphology is described and illustrated, and their distribution is shown on a map.